Religious dimensions of the self in the second century CE - Rüpke, Jörg; Woolf, Greg (Studien und Texte zu Antike und Christentum, 2013)
Hauptbeschreibung Did new senses of the self emerge in the High Roman Empire, and if so what were the religious corollaries? Were such changes connected to processes of institutional change? Could they usefully be described as ""individualisation""? These are the key concerns of the authors of this volume. They address the field of Hellenistic philosophy, medical texts and the literature of the so-called Second Sophistic, which all have been recruited to this debate. Most important, however, religious phenomena are included and brought to the fore. Thus the analysis of concepts of t.